IUCN Red List evaluation of the Orchidaceae endemic to Apulia (Italy) and considerations on the application of the IUCN protocol to rare species - Wagensommer, Robert P.; Medagli, Pietro; Turco, Alessio; Perrino, Enrico V. (Nature Conservation Research: Заповедная наука, 2020)
The conservation status of the ten taxonomically currently recognised orchid species and subspecies (eight in the genus Ophrys, and one each in the genera Epipactis and Serapias) endemic to Apulia (southeast Italy) is presented. Each taxon has been assessed against the internationally accepted IUCN criteria and categories. Of the ten taxa, eight ones are classified as threatened (Endangered or Vulnerable), one as Near Threatened and one as Least Concern. Given that nine of the ten analysed taxa were recently assessed, a comparison with the previous assessments is presented: 67% of the assessed taxa changed their IUCN category. Four taxa (Ophrys murgiana, O. oxyrrhynchos subsp. ingrassiae, O. peucetiae, O. tardans) are now assigned to a higher threat category, while two taxa (Ophrys gravinensis and O. oestrifera subsp. montis-gargani) are now assigned to a lower threat category. These category changes in such a very short time are due to the better knowledge on the number of mature individuals and on the threats affecting the species, and to the discovery of new occurring sites. The most important category change affects Ophrys tardans. The new assessment leads to the category Endangered, whereas in the previous assessment this species was indicated as Least Concern, i.e. as not threatened. Another species with a noteworthy category increase is Ophrys peucetiae, previously indicated as Least Concern and now assigned to the category Vulnerable. The authors discuss these results, highlighting that especially when assessing rare species with a small distribution range against the IUCN protocol, it should be taken into account that the assessment could be influenced (also noteworthy) by the effective knowledge on the distribution, on the population size and on the threats affecting the populations. As a consequence, field work is warmly suggested before assessing the threat category of rare taxa, given that an increased effort in field research often leads to the discovery of new sites and to a better estimation of the number of individuals and of the threats.